The Determinants of Environmental Disclosure in Companies in Indonesia - Maulia, Dina; Yanto, Heri (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this study is to identify the factors that influence environmental disclosure. The study population is 156 companies consisted of companies in the agricultural sector, the consumer goods industry sector, and the basic & chemical industry sector which were listed on the Indonesia Stock Exchange and participated in PROPER 2014-2018. The purposive sampling method was used to determine the research sample in order to obtain 26 company samples or 130 units of analysis. The analysis technique in this study uses multiple linear regression analysis. The results of this study indicate that the level of environmental disclosure in the three corporate sectors in Indonesia is classified as low, due to the absence of standard guidelines for conducting environmental disclosure, so it is still voluntary. The results also show that the variables of board commissioners’ size, size of the audit committee, environmental certification, profitability, and company size have a significant positive effect on environmental disclosure, while leverage has no effect on environmental disclosure. With the low level of corporate environmental disclosure in Indonesia, it is hoped that the government can establish standard, precise, and mandatory guidelines so that companies can further increase information regarding environmental disclosure.